Evaluation of DNA methylation in matched oral swab and tissue specimens from Chinese patients with oral squamous cell carcinoma. Issue 6 (June 2021) - Sun, R.; Zhang, W.-B.; Yu, Y.; Yang, H.-Y.; Yu, G.-Y.; Peng, X.
Abstract: The DNA methylation statuses of the paired box 1 ( PAX1 ) and zinc finger protein 582 ( ZNF582 ) genes have shown promise in the detection of oral squamous cell carcinoma (OSCC). The aim of this study was to investigate the ability of PAX1 and ZNF582 methylation to distinguish OSCC and the adjacent normal tissue among cancer patients. This study included 67 patients with OSCC. The methylation levels of these two genes were analysed in tissue specimens (lesion site and adjacent normal site) and in oral swabs (lesion site and contralateral normal site). Levels of DNA methylation were higher at lesion sites than at the corresponding normal sites. According to receiver operating characteristics curve analysis, the area under the curve for PAX1 and ZNF582 methylation ranged from 0.73 to 0.82. No significant difference was observed between tissue specimens and oral swabs ( PAX1, P  =  0.41; ZNF582, P  = 0.28). For the oral swab, PAX1 methylation was more pronounced in bone invasion ( Z  = 1.988, P  =  0.047), and ZNF582 methylation was more pronounced in early-stage ( Z  = 2.354, P  =  0.02) and well-differentiated tumours ( Z  = 3.731, P  =  0.0002). Hypermethylated PAX1 and ZNF582 are effective biomarkers to distinguish lesion sites and corresponding normal sites in tissue specimens and oral swabs from OSCC patients.